Effect of flow modes on operation characteristics of three‐dimensional non‐isothermal solid oxide fuel cell stack. (26th August 2021) - Fan, Shengliang; Ye, Jianming; Yao, Qiufeng; Wang, Dingbiao; Yang, Lei; Jin, Zunlong
Summary: The three‐dimensional non‐isothermal model of anode‐supported planar solid oxide fuel cell was established. In order to reduce the temperature rise of SOFC in the process of operation and improve the output performance of the stack, this paper studied and compared the operation of SOFC in four different flow modes. The study found that the flow mode has a great influence on the temperature distribution of the SOFC stack. In co‐flow, the temperature increases continuously along the channel length. In the case that oxygen and hydrogen of each cell are in co‐flow, by reversing the flow direction between adjacent cells, the temperature rise of the SOFC stack along the channel direction can be reduced by 26 K, which decreases from 41.2 K to about 15 K. At the same time, the output current density and power density of the SOFC stack are also improved to some extent.